Innovation in research - Azimi, M. (2010)
The present study wanted to find out the relationship between students’ presence in the class and their progress and it also wanted to investigate the role of the students in evaluating their progress. The other purpose was to measure how important the findings would be for other students if their classmates did the study. The subjects were selected by non-random sampling. They were chosen purposefully. The data collection was done by the students. One course was chosen (Reading Comprehension III). Then, the relationship between students' presence in the class and their progress was calculated via Pearson Coefficient of Correlation. The result showed that these two variables were positively correlated.